1990
DOI: 10.1111/j.1365-2141.1990.tb07868.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of recombinant human colony stimulating factor (rh G‐CSF) on stem cells in marrow, spleen and peripheral blood in mice

Abstract: Previously it has been hypothesized that the granulopoietic and erythropoietic lineages may compete for differentiating stem cells. According to this hypothesis one would expect that a stimulation of granulopoiesis by G-CSF administration would lead to a reduction of the stem cell pool and be followed by a decline of erythropoietic progenitor numbers. In addition one would expect an enhanced response of granulopoiesis if G-CSF administration were combined with suppression of erythropoiesis by red cell transfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 11 publications
2
32
0
Order By: Relevance
“…Our data showed that the proliferation and differentiation of erythroid and myeloid phenotypes could be induced from the same source of CD133 + cells, which is consistent with the effects of these cytokines on hematopoiesis [41,42]. Our observation of semi-solid cultures allows us to directly monitor the effect of EPO and G-CSF on the myeloid and erythroid lineage branching-point.…”
Section: Discussionsupporting
confidence: 82%
“…Our data showed that the proliferation and differentiation of erythroid and myeloid phenotypes could be induced from the same source of CD133 + cells, which is consistent with the effects of these cytokines on hematopoiesis [41,42]. Our observation of semi-solid cultures allows us to directly monitor the effect of EPO and G-CSF on the myeloid and erythroid lineage branching-point.…”
Section: Discussionsupporting
confidence: 82%
“…M-CSF = Macrophage-Colony Stimulating Factor; IL-2 = Interleukin 2; IL-6 = Interleukin 6; G-CSF = Granulocyte-Colony Stimulating Factor. In murine models, stem cell factor (SCF) and G-CSF or a combination of the two increases the concentration of colony forming units-spleen (CFU-S) in the peripheral blood [32][33][34][35][36][37]. In the mouse, IL-8 also mobilizes PBSC which have long-term marrow repopulating ability [38].…”
Section: Allogeneic Pbsc Transplants In Animalsmentioning
confidence: 99%
“…In some experiments G-CSF 200 g/kg/day was used. We and others have previously reported [12][13][14][15][16] that at Leukemia these dosages of G-CSF, mice demonstrate similar neutrophilia and progenitor cell mobilisation to that observed in normal humans receiving 5-10 g/kg/day for 5 days. 2 The daily dose was given in two divided doses at 8 am and 6-7 pm each day, and blood and tissues harvested on the morning of the sixth day, 15 h after the final injection.…”
Section: G-csf Administrationmentioning
confidence: 57%
“…In contrast, splenic enlargement is a predictable and prominent in vivo response in mice injected with G-CSF. [12][13][14][15] Splenomegaly is due to increased extramedullary haemopoiesis in both species, but varies between species in relative extent. [11][12][13][14] In mice injected with G-CSF, spleen weight increases in parallel with nucleated cell number, 15 with the increased cellularity directly reflecting the dramatic expansion of splenic myelopoiesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation